Serotonergic Modulation of Nociceptive Circuits in Spinal Cord Dorsal Horn - Bardoni, Rita (Current Neuropharmacology, 2019)
Background: Despite the extensive number of studies performed in the last 50 years, aimed at describing the role of serotonin and its receptors in pain modulation at the spinal cord level, several aspects are still not entirely understood. The interpretation of these results is often complicated by the use of different pain models and animal species, together with the lack of highly selective agonists and antagonists binding to serotonin receptors. Method: In this review, a search has been conducted on studies investigating the modulatory action exerted by serotonin on specific neurons and circuits in the spinal cord dorsal horn. Particular attention has been paid to studies employing electrophysiological techniques, both in vivo and in vitro. Conclusion: The effects of serotonin on pain transmission in dorsal horn depend on several factors, including the type of receptors activated and the populations of neurons involved. Recently, studies performed by activating and/or recording from identified neurons have importantly contributed to the understanding of serotonergic modulation on dorsal horn circuits.
Keywords: descending modulation